2016
DOI: 10.1007/s10597-016-9996-3
|View full text |Cite
|
Sign up to set email alerts
|

The Child and Adolescent Needs and Strengths as an Outcome Measure in Community Mental Health: Factor Analysis and a Validation of the Short Form

Abstract: The goal of the study was to create a short-form measure based on the child and adolescent needs and strengths assessment tool. The measure was designed to be short and easy to use, relevant to youth treated in community-based mental health settings, useful for both treatment planning and program evaluation, and psychometrically valid. Factor analyses of the chosen items revealed two mental health factors and four functioning factors. The mental health factors included internalization and externalization, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Three different variations of CANS were tested: a mental health scale (Anderson et al, 2003 ), a short form (Alamdari & Kelber, 2016 ), and a trauma screener (Kisiel et al, 2018 ). Anderson et al ( 2003 ) found high interrater reliability between caseworkers and researchers on the mental health scale but did not address validity.…”
Section: Results For Individual Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different variations of CANS were tested: a mental health scale (Anderson et al, 2003 ), a short form (Alamdari & Kelber, 2016 ), and a trauma screener (Kisiel et al, 2018 ). Anderson et al ( 2003 ) found high interrater reliability between caseworkers and researchers on the mental health scale but did not address validity.…”
Section: Results For Individual Measuresmentioning
confidence: 99%
“…Anderson et al ( 2003 ) found high interrater reliability between caseworkers and researchers on the mental health scale but did not address validity. The short form showed good concurrent validity with Y-OQ’s somatic and behavior dysfunction subscales (Alamdari & Kelber, 2016 ), while the trauma screener showed good convergent and discriminant validity when compared to TSCC-A and CBCL (Kisiel et al, 2018 ).…”
Section: Results For Individual Measuresmentioning
confidence: 99%
“…Research has documented that the CANS is reliable at the item level allowing notable analytic flexibility (e.g., Anderson et al, 2003 ; Lyons, 2009 , 2022 ). A substantial body of research is developing demonstrating the validity of the CANS in behavioral health, child welfare, and justice settings (Alamdari and Kelber, 2016 ; Juades et al, 2016 ; Vreeland et al, 2020 ; Hong et al, 2021 ). A part of the trauma-informed version of the CANS is a 13-item no/yes coding of trauma experiences as follows:…”
Section: The Implications Of a Tcom Approachmentioning
confidence: 99%